Aplikasi biochar sekam padi dan kombinasi pupuk urea,SP 36 dan KCl terhadap komponen hasil dan hasil tanaman jagung ketan (Zea mays Ceratina) di lahan ultisol - Lusmaniar, Lusmaniar; Oksilia, Oksilia; Nera, Kadek (Universitas Muhammadiyah Mataram, 2022)
Glutinous corn or pulut (Zea mays Ceratina) is a type of corn that is currently in demand by the public. The productivity of glutinous corn is low because corn planting is generally carried out on Ultisol type soils with acidic characteristics and poor in nutrients. This study aims to determine the effect of the application of biochar and inorganic fertilizers (urea, SP 36 and KCl on the yield and yield components of glutinous corn plants. The test method was carried out by factorial RAK with two factors. The first factor was the dose of rice husk biochar (0, 5, 10). and 15 ton ha-1) and the second factor is a combination of inorganic fertilizers (Urea, SP 36 and KCl). The treatment dose of biochar is 10 tons ha-1 and acombination of fertilizers 200 kg ha-1 Urea + 75 kg ha-1 SP-36 + 75 kg ha-1 KCl gave the best yield on plant height, number of leaves, length of cob, weight of cob per plant, weight of cob per plot.